RELIGIÃO, CORPO E EMOÇÃO: EDUCAÇÃO DOS SENTIDOS E HABITUS DE CLASSE NA IGREJA COMUNIDADE DA GRAÇA NO ABC PAULISTA - Antunes Filho, Edemir (2009)
The object of this research study is the Community of Grace, these ten years ago in Sao Bernardo do Campo, Sao Paulo region of the ABC. Is analyzed in this Pentecostal Protestant brotherhood formed mostly by people of middle class, the place of religious emotion and its relation to the education of the senses as offering the assimilation of a habitus and a strong self-control individual demonstrating the effectiveness of the training body through religion. Immersed in a social reality of many changes that cause reconfiguration of religions, in particular type of Pentecostalism studied note that, in the management of symbolic goods, the main ingredient is the emotional attachment to respond to collective and individual demands of public religious. If some years the central cultic of Pentecostal Protestantism was in listening to the sermon and relive the experience of the Christian Pentecost, today the focus here is the emotion that must cross the entire worship. The same occurs in two areas of catechetical privileged church, namely the meeting in the temple called "Knowing the Scriptures" and the meetings of groups in homes. This shift is evident also in the bodies of believers, because they build and shape to the existing social reality and express the experiences in this context. From the observation of religious and catechetical meetings of this church, in this work examines how the religious emotion is constructed, reproduced and distributed, taking into account the social and economic conditions specific to the religious group concerned.(AU)